2012
DOI: 10.1038/nphys2503
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational bar detectors set limits to Planck-scale physics on macroscopic variables

Abstract: Different approaches to quantum gravity, such as string theory 1,2 and loop quantum gravity, as well as doubly special relativity 3 and gedanken experiments in black-hole physics 4-6 , all indicate the existence of a minimal measurable length 7,8 of the order of the Planck length, L p = √h G/c 3 = 1.6 × 10 −35 m. This observation has motivated the proposal of generalized uncertainty relations, which imply changes in the energy spectrum of quantum systems. As a consequence, quantum gravitational effects could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
131
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 34 publications
1
131
0
Order By: Relevance
“…One route to finding such a theory is through the study of phenomenological models, which can motivate conceptual and experimental studies of the interplay between quantum mechanics and general relativity [1][2][3]. Experimental bounds on a variety of such models have been obtained, both from the observed validity of quantum mechanics in a variety of systems and from studies focussed on experimentally testing for such phenomena [4][5][6][7][8][9]. Although, thus far, there has been no experimental evidence of any modifications to quantum mechanics or general relativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One route to finding such a theory is through the study of phenomenological models, which can motivate conceptual and experimental studies of the interplay between quantum mechanics and general relativity [1][2][3]. Experimental bounds on a variety of such models have been obtained, both from the observed validity of quantum mechanics in a variety of systems and from studies focussed on experimentally testing for such phenomena [4][5][6][7][8][9]. Although, thus far, there has been no experimental evidence of any modifications to quantum mechanics or general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several schemes to test the GUP have been proposed. These include optomechanical interactions [22], gravitational bar detectors [6], nanodiamond interferometry [23], and direct measurements on a harmonic oscillator [24]. Several different forms of the GUP have been proposed in the literature [5,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…From more theoretical shores, the discussion has therefore landed on the ground of experimental predictions about the size of these modifications, and several experiments have been proposed to test GUPs in the laboratory. Among the more elaborated proposals are those, for example, of the groups of Brukner, Cerdonio, and Bonaldi [17][18][19]. a e-mail: fabio@phys.ntu.edu.tw b e-mail: casadio@bo.…”
Section: Introductionmentioning
confidence: 99%
“…The upper bounds on the parameter α 0 have been calculated in [13] and it was proposed that GUP may introduce an intermediate length scale between Planck scale and electroweak scale. Recent proposals suggested that these bounds can be measured using quantum optics techniques in [16] and using gravitational wave techniques [17,18] which may be considered as a milestone in quantum gravity phenomenology. In a series of papers, various phenomenological implications of the new model of GUP were investigated [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%